Becoming Christians: Prayers and subject formation in an urban church in China - Huang, Jianbo; Hu, Mengyin (Approaching Religion, 2017)
Prayers in Christianity are often considered to be a theological or pastoral topic; while social scientific studies generally tend to reduce them, like prayers in other religious contexts, to the status of psychological responses bringing comfort to the practitioner, or a collective construction connected with social and cultural institutions. However, what prayer actually is, and what it means to Christians who practise it remains an open issue for further, more intensive and thorough study. Based on fieldwork in an urban church in China, this article provides some perspectives on contemporary Chinese Christians and their prayer life, attempting to elaborate its possible significance, especially in terms of subject-formation processes within these Christians. Meanwhile, this article argues that, in working towards a better understanding of Christians, it is more efficacious to take ‘Christians’ as those who are, rather than a given or acquired identity, or a status of being, engaged in a process of becoming through a practice, or set of practices, which in this case is prayer,. Moreover, in the case of this Chinese Christian church, the practise of prayer also indicates some reflections on the cultural and religious diversity of contemporary Chinese society.